An agro-pastoral household model for the rangelands of East Africa - Thornton, Philip K.; Galvin, K.A.; Boone, Randall B. (Elsevier, 2003)
East Africa contains areas with some of the greatest large mammal biodiversity on the planet. These areas are key natural resources for the economic development of the region. They are also key areas for pastoralists who have co-existed with wildlife for millennia. Increasing populations, conflicts between wildlife and cattle, and the growth of agriculture, are all placing great pressure on these lands This paper describes the development of a pastoralist socio-economic model that is linked to the Savanna ecosystem model. In this way, options and scenarios could be investigated for their impacts not only on the ecosystem but also on pastoralist households and their welfare. The model, named PHEWS (Pastoral Household and Economic Welfare Simulator), tracks the flow of cash and dietary energy in pastoralist households using a simple set of rules. The model was calibrated for the Ngorongoro Conservation Area (NCA), northern Tanzania. The results of two population increase scenarios are presented. Model results indicate that all households in NCA depend to some degree on outside sources of calories, and that pastoralist welfare in NCA, even with small amounts of agriculture allowed, is under severe pressure at current human population levels. Strengths and weakness of the model are discussed, and next steps in its application identified.